Effectiveness of Bromocriptine, Fluoxetine and Nortriptyline in Ameliorating the Negative Symptoms of Schizophrenia - Saied Shoja-Shefti (University of Social Welfare and Rehabilitation Sciences, 2004)
Objective: Negative symptoms in schizophrenia are among the important barriers against Rehabilitation of Schizophrenic patients. Adjunctive drugs and social skills training can be used for reducing the severity of such symptoms. In this research we studied the efficacy of Bromocriptine, Fluoxetine, and Nortriptyline in reducing Negative symptoms of Schizophrenia. This is for the first time that Nortriptyline is being appraised regarding to this matter. Materials & Methods: One hundred Schizophrenic patients in Razi psychiatric hospital were selected randomly and divided into four groups to take part in an open and cotrolled study. These groups were treated respectively with Bromocriptine 2.5 mg, Fluoxetine 20 mg, Nortriptyline 25 mg, and finally placebo, in addition to their current treatments (including standard Antipsychotics). After three weeks the dosage of aforesaid drugs were doubled and after another three weeks they tapered and the study terminated. Existence and severity of Negative symptoms had been appraised at the beginning )and before starting these drugs( and at the end of the third week and finally at the end of the sixth week by the scale of SANS. During this course (Six week) only one patient in the Fluoxetine group due to his reluctance and another one in the placebo group due to cardiac accident were excluded. No other major side effects were seen among the other patients. The data about variables were statistically surveyed by Z and Chi-Square (x2 -test) formula.  Results: Negative symptoms in the aforesaid groups were reduced with placebo, Bromocriptine, Fluoxetine, and Nortriptyline Respectively in 37.5 %, 44 %, 62.5 % and 80 % percent of patients in their related groups. This reduction in the majority of cases was restricted to only 20 % percent from the baseline. Only in three cases in the Nortriptyline's group and one in the Bromocriptine's group this reduction was up to 40% percent. There was no difference between mild to moderate and severe symptoms regarding to respond to treatment. This reduction was occurred discretely among different five clusters of symptoms. Conclusion: Bromocriptine, Fluoxetine and Nortriptyline Reduced Negative symptoms in Schizophrenic patients. Among them in relation with placebo the Nortriptyline was the most effective one (P<0.005) and Bromocriptine the weakest (P<0.75), and Fluoxetine between this two (P<0.1). There was no significant differences between Nortriptyline and Flouxetine on one hand (P<0.25), and Fluoxetine and Bromocriptine (P<0.25) on the other hand. BUT Nortriptyline was remarkably more effective than Bromocriptine (P<0.01).